Comrades, clients and cousins : colonialism, socialism and democratization in Sao Tome and Principe - Seibert, Gerhard, 1954- (Leiden : Brill, 2006)
Colonized in the late 15th century, São Tomé and Príncipe were ruled by Portugal for 500 years, one of the longest periods of European domination in colonial history. In fact, during this period the Portuguese colonized the islands twice. Both colonizations were driven by the production of tropical cash crops; however, they occurred under rather different circumstances. Its long history as a plantation colony has made this African archipelago in many aspects more akin to the small Caribbean states. Since its decolonization in 1975 the small and impoverished country has experienced two fundamental changes to its political and economic system in a short period of 15 years. After embracing socialism and a centralized economy at independence, in 1990 the country introduced liberal democracy and a free-market economy. This case study analyses the course of political and economic changes in postcolonial São Tomé and Príncipe. The central issue of the book is to which extent institutional changes based on external models altered local patterns of political culture and of doing politics. In addition, it examines the outcome of the consecutive economic policies and development approaches patterned on theses models. This second edition has been completely revised and updated for the period of 1998-2005, including the recent developments in the country's emerging oil sector.
Formation and recolonization of an African Creole society -- From the origins of forro nationalism to independence -- The socialist one-party regime -- Political transition and economic reform -- Governance, conflict, and public property under the democratic system -- Structural adjustment and economic performance under democratic rule -- Political pluralism and competitive elections -- Party trajectories and presidential elections -- Local dimensions of politics : kinship, rumours, and pamphlets.
Previous edition published in 1999 by CNWS Publications, Leiden University.
Updated to include data on the period of 1998-2005.
Includes bibliographical references (pages 557-574) and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
Keywords: Democratization -- Sao Tome and Principe; Sao Tome and Principe -- Politics and government; Sao Tome and Principe -- Economic policy; Sao Tome and Principe -- History; Démocratisation -- São Tomé et Príncipe.; POLITICAL SCIENCE -- Political Process -- General; Democratization; Economic policy; Politics and government; Sao Tome and Principe; History